Mapping Research on Artificial Intelligence in Education: A Bibliometric Analysis - Hidayat, M Topit; Armiati, Armiati; Noviani, Cyindi (Journal of Innovation in Educational and Cultural Research, 2026)
This research aims to explore the development of academic publications on artificial intelligence (AI) in education. Using bibliometric analysis, this research examines scientific publications indexed in Scopus from 2020 to 2024. The primary keyword utilized for data collection is "artificial intelligence in education." The analysis reveals a significant increase in publications featuring this keyword during the specified period. Europe emerged as the leading region in AI-related educational research, with the Netherlands contributing the most scientific publications on this topic. Notably, Ismaila Temitayo Sanusi was identified as the most prolific researcher, while Davy Tsz Kit Ng recorded the highest number of citations. Among publication venues, the journal Computers and Education: Artificial Intelligence was identified as the platform with the largest volume of publications on this subject. These findings underscore the growing academic interest in AI in the education sector. Furthermore, this research highlights opportunities for further exploration in less-studied areas, such as AI education, AI literacy, curriculum design, and the impact of AI on learning outcomes. These gaps highlight the necessity for further research on effectively integrating AI to improve global educational practices.